Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1177/08862605231175519
|View full text |Cite
|
Sign up to set email alerts
|

“There Are Good and Bad Elements to It for Sure”: Students’ and Faculty/Staff’s Perceptions of the Title IX Mandated Reporting Policy

Abstract: Faculty, staff, and students employed by or who serve as representative of universities in the United States are required by the Title IX federal law to report all instances of sexual harassment, discrimination, and sexual assault on college campuses. Despite the well-intended purpose of the Title IX regulations, less is known about campus communities’ experiences and perceptions of this “mandated reporting,” and its influence on disclosure. This exploratory mixed-methods study examines student ( n = 88) and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, empirical research suggests that even IHEs that do have a publicly accessible policy may not be well understood by members of the campus community. Studies of IHE employees have consistently found that employees are likely to be generally aware of their reporting requirements, and intend to fulfill them, but they lack important logistical knowledge about this role (e.g., where and how to report; Brubaker & Mancini, 2017; Johnson et al, 2023; Koon-Magnin & Mancini, 2023; Mancini & Koon-Magnin, 2023). For example, IHE employees frequently report receiving training about their institution’s MR policy, but concrete knowledge on the policy is variable (e.g., to whom they must report), and many employees indicate that they are unsure if they are a mandatory reporter (Koon-Magnin & Mancini, 2023; Mancini & Koon-Magnin, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, empirical research suggests that even IHEs that do have a publicly accessible policy may not be well understood by members of the campus community. Studies of IHE employees have consistently found that employees are likely to be generally aware of their reporting requirements, and intend to fulfill them, but they lack important logistical knowledge about this role (e.g., where and how to report; Brubaker & Mancini, 2017; Johnson et al, 2023; Koon-Magnin & Mancini, 2023; Mancini & Koon-Magnin, 2023). For example, IHE employees frequently report receiving training about their institution’s MR policy, but concrete knowledge on the policy is variable (e.g., to whom they must report), and many employees indicate that they are unsure if they are a mandatory reporter (Koon-Magnin & Mancini, 2023; Mancini & Koon-Magnin, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of college students have found that most report some level of awareness of employee reporting requirements when queried in a survey or presented with scenarios describing sexual violence (e.g., Johnson et al, 2023; Newins et al, 2018; Newins & White, 2018), but students report less awareness of mandatory reporting policies than employees (e.g., Johnson et al, 2023). Moreover, a recent a qualitative study with graduate student survivors examined participants’ experiences with mandatory reporting (Cipriano et al, 2023); few survivors in this study knew that they were disclosing to a mandated reporter before they disclosed, and those mandated reporters lacked logistical knowledge beyond their requirement to report (e.g., what would happen after the report was made), which caused survivors significant psychological distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mandatory reporting, also known as compelled disclosure, is one common policy on campuses requiring certain employees to report disclosures of student experiences of SV to university officials, regardless of whether a student wants to report (Holland et al, 2018 ; Newins & White, 2018 ). Research on the student and faculty/staff support of mandatory reporting policies, and their effects on SV prevention and intervention, is varied (Holland et al, 2018 ; Johnson et al, 2023 ). Mandatory reporting policies that limit the number of people required to report SV and offer autonomy and flexibility are most preferred by survivors (Holland, Cipriano et al, 2021 ), but are not necessarily aligned with how policies are practically implemented (Wiersma-Mosley & DiLoreto, 2018 ).…”
Section: Introductionmentioning
confidence: 99%